LEGENDA SUMUR SUMBERGEDE, DESA SUMBERGEDE KECAMATAN KEPOHBARU, KABUPATEN BOJONEGORO (KAJIAN STRUKTUR NARATIF, NILAI BUDAYA DAN RESEPSI MASYARAKAT) - Ayu, Setia Sauma; Sariban, Sariban; Selirowangi, Nisaul Barokati (Hasta Wiyata, 2020)
The purpose of this study is to describe the narrative structure, cultural values, and community reception of the Sumbergede Well Legend, Sumbergede Village, Kepohbaru District, Bojonegoro Regency. The method used in this research is descriptive qualitative method. This research data in the form of interviews obtained from informants selected by researchers. The data collection of this study used thetechnique to Observationobserve the research sites and resource persons who would be asked for interviews, recording techniques, text transcriptions, translation techniques, documentation techniques. The results of research conducted by researchers at the Sumbergede Well are a Legend Well that is trusted by the Sumbergede Village community as an effective place to fertilize plants and cure diseases. According to the elder of Sumbergede Village, named Mbah Guru Noerlan, a 73 year old man. According to the elder that this well is a well that is believed by the community as a place of Kramat.